The Role of the Dialogical Patrol of Sabhara's Dialogue Use to Prevent Curanmor Action in the Legal Area of The Polresta Sidoarjo - Ramadhan, Danny (Police Studies Review, 2021)
This research based on the increasing number of curanmor cases in Indonesia. In Sidoarjo Police, although it is not as high as the number of curanmor in other Polresta jurisdictions, the opportunity for curanmor action in this jurisdiction is quite high. The aim of this research is to see how the role of the Sabhara unit dialogic patrol is to prevent curanmor actions in the legal area of the Sidoarjo Police and what are the factors that affect the role of the Sabhara unit dialogic patrol in preventing criminal acts of curanmor cases in the Sidoarjo Police jurisdiction. Researchers use routine activity theory to see an overview of curanmor actions in this jurisdiction. The researcher used role theory, POAC management theory and the Police Perkap in describing the role of dialogical patrols in the jurisdiction of the Sidoarjo Police. Finally, the researcher uses The Six M management theory to identify the factors that influence the role of dialogical patrols in this jurisdiction. This study uses a qualitative approach with a descriptive analysis method. The sources of information were obtained from primary data, namely interviews with KBO, Wakasat Sabhara, Kanit Sabhara, and communities in the jurisdiction of the Sidoarjo Police, while secondary data was obtained from internal documents of the Sidoarjo Police. The result of this research is that the Dialogical Patrol which is carried out routinely by the Sabhara Unit of the Sidoarjo Police has a role in preventing curanmor actions. This is of course based on several factors that support this role so that this patrol activity can run according to the provisions in order to achieve its goals. However, there are some of the most important obstacles that come from the human factor itself. Both in terms of the police and the community. Researchers suggest that the police can improve the quality of its members so as not to become an obstacle in carrying out patrols in the future.